MYB and MYBL1 in adenoid cystic carcinoma: diversity in the mode of genomic rearrangement and transcripts. (June 2018) - Togashi, Yuki; Dobashi, Akito; Sakata, Seiji; Sato, Yukiko; Baba, Satoko; Seto, Akira; Mitani, Hiroki; Kawabata, Kazuyoshi; Takeuchi, Kengo
Abstract MYB-NFIB andMYBL1-NFIB have been reported in ~60% of adenoid cystic carcinoma cases, but driver alterations in the remaining ~40% of adenoid cystic carcinoma remain unclear. We examined 100 adenoid cystic carcinoma cases forMYB andMYBL1 locus rearrangements by fluorescencein situ hybridization (FISH) with originally designed probe sets using formalin-fixed paraffin-embedded materials. Approximately one-third of samples were also analyzed by fusion transcript-specific RT-PCR and capture RNA sequencing. In the 27 cases with frozen materials, MYB-NFIB andMYBL1-NFIB fusion transcripts were detected in 9 (33%) and 6 cases (22%) by RT-PCR, respectively. Meanwhile, high expression ofMYB (18 cases, 67%) orMYBL1 (9 cases, 33%) was detected in all 27 cases in a mutually exclusive manner, regardless of its form (full-length, truncation, or fusion transcript). Interestingly, genomic rearrangements around the corresponding highly-expressed gene were observed in all 27 cases by FISH, suggesting a causative relationship between genomic rearrangements and gene expression. Among the 100 cases, including additional 73 cases, 97 harbored genomic rearrangements in theMYB (73 cases) orMYBL1 locus (24 cases) including 10 cases with atypical FISH patterns undetectable through ordinary split FISH approaches: breakpoints far distant fromMYB (5 cases) and a smallNFIB locus insertion into theMYB (3 cases) orMYBL1 locus (2 cases). In clinicopathological analyses, histological grade, primary tumor size, and lymph node metastasis were identified as prognostic factors, whereasMYB/MYBL1 rearrangements were not, but were associated with histological grade. In the present study, MYB orMYBL1 locus rearrangement was detected in nearly all adenoid cystic carcinoma cases, and therefore it would be a good diagnostic marker for adenoid cystic carcinoma. However, fusion transcript-specific RT-PCR forMYB-NFIB andMYBL1-NFIB and ordinary split FISH assays forMYB andMYBL1 were less sensitive, and thus detection methods should be judiciously designed because of the diversity of rearrangement modes in adenoid cystic carcinoma.